A high-performance three-dimensional Ni–Fe layered double hydroxide/graphene electrode for water oxidation1. Issue 13 (7th April 2015) - Yu, Xiaowen; Zhang, Miao; Yuan, Wenjing; Shi, Gaoquan
<x xml:space="preserve">Abstract</x> Ni–Fe layered double hydroxide nanoplates loaded on a three-dimensional electrochemically reduced graphene oxide electrode for efficient water oxidation, exhibiting higher activity, kinetics, and stability than those of the IrO2 catalyst.